A Limited Liability Company's Wealth Status in Islamic Law - Fatika Sari (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
This study focuses on the wealth of limited liability companies based on Islamic Law. The problem defined is how the validity of the Limited Liability Company and the position of the wealth by Limited Liability Company are based on Islamic Law. The research method used is normative with a statute approach and conceptual approach. The method used is a literature study which uses a descriptive analysis. The results of the study conclude that the validity of a Limited Liability Company can be equated with syirkah mal 'inan since a cooperation agreement between two or more people in the form of a commodity or an association in all forms of commodities. Separated assets and the capital of a Limited Liability Company can be categorized as mal ashal and the company result are mal tsamarah.